Spice Cookies Sdn Bhd / Farrah Azwani Mohd Ridzwan ... [et al.] - Mohd Ridzwan, Farrah Azwani; Datu Rainier, Dayang Rozelana; Prichard, Cleopatra; Shukor, Muhammad Zaki (2014)
The name of our company is Spice Cookies Sdn Bhd that selling spice cookies which is full of warm spices. The business is in form of partnership which consists of four members. Each partner contributes a certain amount of capital as agreed in agreement. There are no sleeping partners and all are entitled to participate in the business management. We agreed that Dayang Rozelana Binti Datu Rainier as the General Manager and Finance Manager, Muhammad Zaki Bin Shukor as the Administration Manager, Farrah Azwani Binti Mohd Ridzwan as the Operational Manager and lastly Cleopatra Prichard as the Marketing Manager. Our vision is to be the number one retailer that sells the best spice cookies in Sabah by year 2024. Our spice cookies is in demand since our cookies is different from others in terms of ingredients and competitively priced whereby the setting of the price of product based on competitors' price. Our business is located at Suria Sabah whereby this place is on high growth product driven by current social trends such as Big Apple Donut, Yoyo Cafe and many more. Also, the majority of shops are local giving the Suria Sabah a unique character that is different from most shopping complexes, and from this we can promote our spiced cookie that most of the ingredients is focused on spices for example cinnamon and onions.